Usefulness of the electrocardiogram and cardiac magnetic resonance to differentiate tachycardia induced cardiomyopathy from dilated cardiomyopathy in patients admitted for heart failure. (13th July 2021) - Vera Sainz, A; Cecconi, A; Martinez-Vives, P; Olivera, MJ; Hernandez, S; Tejelo, J; Lopez Melgar, B; Rojas Gonzalez, A; Diez-Villanueva, P; Salamanca, J; Caballero, P; Alfonso, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: In patients admitted for heart failure (HF) with reduced left ventricular ejection fraction (LVEF) and a concomitant high-rate supraventricular tachyarrhythmia (SVT) it is challenging to predict LVEF recovery after heart rate control and distinguish tachycardia-induced cardiomyopathy (TIC) from dilated cardiomyopathy (DC). The role of cardiac magnetic resonance (CMR) and the electrocardiogram (ECG) in this setting remains unsettled. Methods: Forty-three consecutive patients admitted for HF due to high-rate SVT and LVEF <50% undergoing CMR in the acute phase were retrospectively included. Those who had LVEF >50% at follow up were classified as TIC and those with LVEF <50% were classified as DC. Clinical, laboratory, CMR and ECG findings were analyzed to predict LVEF recovery. Results: Twenty-five (58%) patients were classified as TIC. Patients with DC had wider QRS (121.2 ± 26 vs 97.7 ± 17.35 ms; p = 0.003). On CRM the TIC group presented with higher LVEF (33.4 ± 11 vs 26.9 ± 6.4% p = 0.019) whereas late gadolinium enhancement (LGE) was more frequent in DC group (61 vs 16% p = 0.004). On multivariate analysis, QRS duration ≥100 ms (p = 0.027), LVEF < 40% on CMR (p = 0.047) and presence of LGE (p = 0.03) were identified as independent predictors of lack of LVEF recovery. Furthermore, during clinical follow-up (median 60 months) DC patients were admitted more frequently for HF (44% vs 0%; p < 0.001) than TIC patients (Figure 1). Conclusion: In patients with reduced LVEF admitted for HF due to high-rate SVT, QRS duration ≥100 ms, LVEF <40% on CMR and presence of LGE are independently associated with lack of LVEF recovery and worse clinical outcome.